The Effect of Workload on Work Productivity Oil Palm Harvester - Hasanah, Wirdatun; Susanti, Nofi; Agustina, Dewi (GLOBAL HEALTH SCIENCE GROUP, 2024)
Work productivity at work is very important for a company to produce a product to achieve targets and as a form of consideration to achieve success in a company. The purpose of this study was to determine the effect of workload on the labor productivity of oil palm harvesters. The research method used quantitative research with Cross Sectional design and data analysis on univariate tests using frequency distribution tables and Paired tests on pulse samples with sig. < 0.05 values. A sample of 48 respondents who were oil palm harvesters at PT. Merbaujaya Indahraya, Aek Kuo District, using total sampling. The measurements in this questionnaire use the Likert scale, and check the pulse on the arteries in the respondent's wrist, and see the results of the achievements obtained by the respondent. The results showed that the workload had a positive and significant effect on the work productivity of oil palm harvesters at PT Merbaujaya Indahraya, Aek Kuo District, with a significance value (sig) of 0.000 < 0.05. This study came to the conclusion that the work productivity of oil palm harvesters at PT Merbaujaya Indahraya is in the good category, but there must be improvements to increase the work productivity of oil palm harvesters to remain stable and increase for the success of a company.